ANALISIS BLIBLIOMETRIK: PENGARUH REPRESENTASI SUPREMESI KULIT PUTIH DAN TERPAAN IKLAN SCARLETT WHITENING TERHADAP PENERIMAAN INFORMASI OLEH REMAJA PEREMPUAN - Alifiah Mulia Wulandari; Totok Wahyu Abadi; Laila Nur Hidayati; Safira Ramadhani Putri; Febriayu Vina Kurniasari (Jurnal Ranah Komunikasi, 2023)
Today's modern technology allows audiences to reach information faster every day through various platforms, not even teenagers. The rapid development of the beauty product business has caused major changes in the market sector. Beauty products are not only about cosmetics but also include body care products. Various brands emerged because the appearance of women is often associated with aesthetic value, one of which is Scarlett Whitening. Scarlett made various efforts to carry out marketing strategies to attract consumers' buying interest. Scarlett Whitening cooperates with a number of public figures such as influencers to several Korean celebrities. With persuasive language and content, content that often appears on social media can influence the mindset of young girls that beautiful people are those with white skin. The results of this study show that social media is a platform that has the power to market lotion products to consumers and brand image. Celebrities in their presence on social media have contributed to endorsing scarlet whitening products. There are three interesting agendas from the results of this Bibliometric study, namely the representation of white supremacists, exposure to advertising, and adolescent acceptance of scarlet whitening information.